Modified zinc-iron-manganese-based layered oxides, their preparation and use in sodium-ion batteries

CN122930850APending Publication Date: 2026-10-16CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510418277.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-03
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

即使如此,现有技术仍难于充分发挥铁的氧化还原活性,此外,也难于兼顾铁性能高效释放所面临的铁溶出和铁迁移难于同步兼顾控制等问题

Benefits of technology

[0048] This invention provides a novel modified zinc-iron-manganese base oxide, which is based on a matrix, Mn3O4, and Na. b The combination of material A, its hierarchical structure, and content enables synergy, allowing the electrochemical activity of iron to be released. Furthermore, it effectively reduces iron dissolution and migration, thus exhibiting excellent capacity, high rate capability, and long cycle life even under ultra-low nickel content or even nickel-free conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930850A_ABST
    Figure CN122930850A_ABST
Patent Text Reader

Abstract

The application belongs to the field of battery materials, and particularly relates to a modified zinc-iron-manganese-based layered oxide and preparation and application thereof. a Zn x Fe y Mn z M 1‑x‑y‑z O2; wherein M is a transition metal element, 0.8 < a < 1.02, 0.05 < x < 0.4, 0.34 < y < 0.8, and 0.1 < z < 0.5; the coating layer comprises a first coating layer coated on the surface of the substrate and a second coating layer coated on the first coating layer, wherein the material of the first coating layer is Mn3O4, and the material of the second coating layer is Na b A, A is a non-metal anion or an anion group; b is the absolute value of the valence of A; in the modified zinc-iron-manganese-based layered oxide, Mn3O4 is 0.5-5% of the molar amount of the substrate, and Na b A is 0.2-3% of the molar amount of the substrate. The material can exhibit excellent capacity and high-rate long cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of chemical power sources, and specifically relates to the field of layered oxide positive electrode active materials for sodium-ion batteries. Background Art

[0002] As the market scale of the new energy field continues to expand, the global demand for lithium-ion batteries keeps increasing. However, the limited and unevenly distributed lithium resources have seriously hindered the further development of the new energy field. Sodium-ion batteries have a working principle similar to that of lithium-ion batteries, while sodium resources are abundant, widely distributed, and lower in cost. Sodium-ion batteries have shown great market application prospects and have gradually become a research hotspot in the industry.

[0003] Layered oxide materials for sodium-ion batteries have characteristics such as high capacity, high compaction density, and ease of production, and are a very promising positive electrode material. For example, Chinese patent literature with publication number CN119230774A discloses a layered oxide positive electrode material for sodium-ion batteries, with a general structural formula of NaMO@NaMO, where 0.2<x<1; 0<a≤1; 0<b≤1; wherein M is selected from at least one of Ni, Mn, Fe, Co, Cu, Ti, V, Cr, Mg, Zn, K, Al, Ca, Mo, Ru, Nb, Ir and Zr. Among layered oxide materials, iron-containing materials have great cost advantages and are materials with great commercial prospects. Some iron-containing layered oxide materials are also disclosed in the prior art. For example, Chinese patent literature with publication number CN119230816A discloses a multi-cation co-doped O3-NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 layered sodium-ion battery positive electrode material, whose chemical formula is NaM x Ni (1 / 3-x) N y Fe (1 / 3-y) Mn 1 / 3 O2, (wherein M=Zn, Cu, Mg, etc.; N=Co, Ce, Ga, Al, Cr, etc.; 0≤x≤0.33, 0≤y≤0.33).

[0004] Although iron-containing layered oxide positive electrode materials have great application prospects and economic value, the iron content of existing materials is still relatively low, and a relatively high nickel content is still required to exert the performance of the materials. Even so, the prior art still has difficulty in fully exerting the redox activity of iron, and in addition, it is difficult to simultaneously address and control the problems such as iron dissolution and iron migration that are faced in the efficient release of iron performance. Contents of the Invention

[0005] To address the problems existing in existing materials, the primary objective of this invention is to propose a modified zinc-iron-manganese base oxide, aiming to provide a novel positive electrode active material that is high in iron and low in nickel, can effectively utilize the electrochemical activity of iron, and can effectively control the associated iron dissolution and migration problems, thereby achieving excellent performance such as high capacity, high rate capability, and long cycle life.

[0006] The second objective of this invention is to provide a method for preparing modified zinc-iron-manganese base oxide and its application in sodium-ion batteries.

[0007] A third objective of the present invention is to provide a sodium-ion battery comprising the modified zinc-iron-manganese base oxide, and the positive electrode and positive electrode material thereof.

[0008] Previous studies have shown that the combination of zinc, manganese, and iron helps to fully utilize and release the performance of layered materials; however, it also increases iron dissolution and migration in the bulk matrix, making it difficult to achieve the expected performance. To address the challenges of balancing ferroelectrochemical activity activation and stability with iron dissolution and migration in zinc-iron-manganese layered oxides, this invention, after in-depth research, provides the following improvement:

[0009] A modified zinc-iron-manganese base oxide comprises a matrix and a coating layer, wherein the chemical formula of the matrix is ​​Na. a Zn x Fe y Mn z M 1-x-y-z O2; where M is a transition metal element, 0.8 <a<1.02,0.05<x<0.4,0.34<y<0.8,0.1<z<0.5;

[0010] The coating layer includes a first coating layer coated on the surface of the substrate and a second coating layer coating the first coating layer, wherein the material of the first coating layer is Mn3O4; and the material of the second coating layer is Na. b A is a nonmetallic anion or anionic group; b is the absolute value of the valence of A;

[0011] In the modified zinc-iron-manganese matrix oxide, Mn3O4 accounts for 0.5-5% of the matrix molar amount; Na b A represents 0.2% to 3% of the matrix molar amount.

[0012] To fully utilize the activity of iron in iron-containing layered oxides, this invention is the first in the industry to provide a zinc-iron-manganese layered oxide approach. Furthermore, addressing the more prominent iron dissolution-migration problem faced by zinc-iron-manganese layered oxides, it innovatively pre-coats its surface with Mn3O4, and then combines it with Na... bThe second coating of A can thus be based on the matrix, Mn3O4, and Na. b The combination of material A, its hierarchical structure, and content enables synergy, fully leveraging the redox activity of iron. Furthermore, it effectively reduces iron dissolution and migration, thus exhibiting excellent capacity, high rate capability, and long-cycle stability (such as capacity retention stability and average voltage retention) even under ultra-low nickel content or even nickel-free conditions.

[0013] In this invention, the matrix contains, but is not limited to, one or more of Ni, Co, Ca, Mg, Al, Sc, Ti, V, Cr, Cu, Zr, Nb, Mo, Ta, W, and Re.

[0014] Preferably, M is a combination of Mg and Al, or a combination of Ni and Mg, or a combination of Cu, Ni, and Mg. When a combination of M is used, the individual element accounts for 10-80% of the molar amount of M. Research in this invention shows that the preferred M can further synergistically improve the material's performance.

[0015] Preferably, a is 0.85–0.93, x is 0.15–0.25, y is 0.5–0.55, and z is 0.25–0.3.

[0016] In this invention, in the matrix, A is F. - Cl - B4O7 2- BO3 3- P2O7 4- PO4 3- At least one of them.

[0017] Preferably, A contains at least PO4. 3- Further preferred formulations include PO4. 3- and B4O7 2- Furthermore, the aforementioned PO4 3- and B4O7 2- The molar ratio is 1:0.1 to 2; more preferably 1:0.5 to 1.5. In this invention, under the preferred ratio A, better synergy can be obtained, and the performance of the material can be further improved.

[0018] In this invention, the thickness of the Mn3O4 coating layer in the modified zinc-iron-manganese base oxide is 1–5 nm.

[0019] (Further, it can be 2-4 nm), Na b The thickness of the A coating layer is 2-15 nm (or even 4-10 nm).

[0020] In this invention, in the modified zinc-iron-manganese matrix oxide, Mn3O4 accounts for 2-4% of the matrix molar amount; Na b A is 1-2% of the matrix molar weight. More preferably, Mn3O4 is 3-4% of the matrix molar weight; Na... b A is 1 to 1.5% of the matrix molar amount.

[0021] This invention also provides a method for preparing the modified zinc-iron-manganese base oxide, comprising mixing a matrix and Mn3O4, calcining the mixture to coat the matrix with an Mn3O4 layer; subsequently mixing the mixture with an A precursor and calcining the mixture, followed by rapid cooling to coat the Mn3O4 layer with Na in situ. b Layer A is used to prepare the modified zinc-iron-manganese base oxide;

[0022] The precursor of A is the acid and / or ammonium salt of A.

[0023] This invention innovatively employs Mn3O4 to pre-coat the matrix, followed by a second-stage in-situ coating with precursor A and rapid cooling. This effectively controls the phase composition of the coating layer and forms coating materials with complete surfaces and tight interfacial bonding. Through the combination of the matrix and the coating layer, the electrochemical activity of iron in the material can be significantly enhanced, and problems such as iron migration and dissolution caused by high iron activity can be solved. This results in a significant improvement in the capacity and high-rate, long-cycle stability of the material at ultra-low nickel content.

[0024] In this invention, the matrix can be synthesized based on known preparation methods while ensuring the chemical formula is maintained. For example, as an optional method, the matrix is ​​obtained by a two-stage heat treatment of a mixed raw material comprising a sodium source, a zinc source, an iron source, a manganese source, and an M source; wherein the two-stage heat treatment includes a first-stage heat treatment holding process at a temperature of 300–700°C (preferably 400–550°C) and a second-stage heat treatment holding process at a temperature of 800–1200°C (preferably 950–1100°C; more preferably 1040–1060°C).

[0025] In this invention, the sodium source, zinc source, iron source, manganese source and M source are each at least one of the oxides, carbonates, nitrates and organic acid salts of their respective metal elements.

[0026] For example, the sodium source can be at least one of sodium carbonate, sodium nitrate, sodium bicarbonate, sodium hydroxide, sodium oxalate, sodium acetate, sodium peroxide, and sodium nitrite; further, it can be at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium oxalate, and sodium acetate; and even further, it can be a combination of sodium carbonate, sodium bicarbonate, and sodium hydroxide.

[0027] In this invention, the Zn, Fe, Mn, and M in the sodium source, zinc source, iron source, manganese source, and M source are in stoichiometric ratios according to chemical formulas, and the Na in the Na source is 1 to 1.1 times the stoichiometric molar amount.

[0028] Preferably, the heat treatment holding time for the first stage is 3 to 8 hours (preferably 5 to 6 hours), and the heat treatment holding time for the second stage is 7 to 20 hours (preferably 15 to 18 hours).

[0029] In this invention, the matrix material and Mn3O4 can be mixed and calcined to form the first coating layer.

[0030] In this invention, Mn3O4 phase material is innovatively used to calcine and coat the zinc-iron-manganese matrix. This facilitates the combination with subsequent coating processes, helps control the migration and exudation of highly active iron in the matrix, and thus helps to synergistically improve the capacity and long-cycle performance at high rates of the prepared material.

[0031] In this invention, the calcination temperature is 300–700℃, preferably 600–650℃.

[0032] Preferably, the holding time at the calcination temperature is 3 to 8 hours, and more preferably 6 to 8 hours.

[0033] In this invention, the first coating material and precursor A are mixed to facilitate the surface physicochemical properties of the first coating material and the in-situ targeting effect between precursor A, thereby forming the second coating layer. This is further combined with subsequent rapid cooling treatment, which helps to optimize the phase structure and interface bonding of the first and second coating layers, thereby synergistically solving the migration and extravasation of highly active iron in the matrix material.

[0034] In this invention, the calcination temperature is 300–700°C, preferably 400–550°C.

[0035] Preferably, the holding time at the calcination temperature is 3 to 8 hours, and more preferably 5 to 6 hours.

[0036] Preferably, rapid cooling is performed after roasting while the food is still in contact with a cooling medium.

[0037] Preferably, the cooling medium is at least one of liquid nitrogen and dry ice.

[0038] Preferably, the initial temperature difference for rapid cooling is above 200°C.

[0039] This invention also provides a modified zinc-iron-manganese base oxide prepared by the aforementioned method.

[0040] In this invention, based on existing ideas and methods, the modified zinc-iron-manganese base oxide described in this invention can be used as a positive electrode active material, thereby obtaining the required sodium-ion battery and its related components and materials (such as positive electrode, positive electrode material, etc.).

[0041] For example, as part of the same inventive concept, the present invention also provides a positive electrode material for a sodium-ion battery, including a positive electrode active material, wherein the positive electrode active material includes the modified zinc-iron-manganese base oxide described in the present invention.

[0042] Preferably, the content of the modified zinc-iron-manganese base oxide in the positive electrode active material is above 50 wt.%; more preferably, it can be the modified zinc-iron-manganese base oxide.

[0043] In this invention, the positive electrode material may also contain a conductive agent and a binder. The conductive agent and binder can be materials known in the industry; for example, the conductive agent can be a carbonaceous conductive agent known in the industry. The binder can be PVDF, CMC, etc.

[0044] In this invention, the content of the conductive agent in the positive electrode material is less than 15 wt.% (for example, it can be 5 to 15 wt.%); the content of the binder is less than 15 wt.% (for example, it can be 5 to 15 wt.%).

[0045] The present invention also provides a positive electrode for a sodium-ion battery, comprising a current collector and a positive electrode material composite thereon, wherein the positive electrode material is the positive electrode material described in the present invention.

[0046] The present invention also provides a sodium-ion battery, comprising a positive electrode and a negative electrode, and a barrier material disposed between the positive electrode and the negative electrode, characterized in that the positive electrode is the positive electrode of the present invention.

[0047] Beneficial effects:

[0048] This invention provides a novel modified zinc-iron-manganese base oxide, which is based on a matrix, Mn3O4, and Na. b The combination of material A, its hierarchical structure, and content enables synergy, allowing the electrochemical activity of iron to be released. Furthermore, it effectively reduces iron dissolution and migration, thus exhibiting excellent capacity, high rate capability, and long cycle life even under ultra-low nickel content or even nickel-free conditions.

[0049] This invention also provides a method for preparing the modified zinc-iron-manganese matrix oxide, which innovatively pre-coats Mn3O4 onto a matrix with the aforementioned elemental characteristics, and then performs an in-situ second-stage coating and rapid cooling treatment with the A precursor raw material. This effectively controls the phase composition of the coating layer and forms coating materials with complete surfaces and tight interfacial bonding. Through the combination of the matrix and the coating layer, the iron activity of the material can be significantly enhanced, and problems such as iron migration and dissolution caused by high iron activity can be solved. It can also significantly improve the capacity and high-rate long-cycle stability of the material even at ultra-low nickel content.

[0050] This invention also shows that combining the parameters such as M and A in the aforementioned combination can further synergistically enhance the material's performance.

[0051] The layered oxide sodium-ion battery cathode material of this invention, through component design, can fully utilize the redox activity of iron and exhibits high reaction reversibility and structural stability. The surface coating layer, on the one hand, suppresses interfacial side reactions and transition metal dissolution during cycling, improving cycle performance; on the other hand, it improves air stability, facilitating the storage and processing of the cathode material; and the coating process eliminates residual sodium on the material surface, further enhancing the material's electrochemical performance. Furthermore, the cathode material preparation method provided by this invention has a simple process flow, high production efficiency, and is suitable for large-scale production. Attached Figure Description

[0052] Figure 1 The image shows the XRD pattern of the cathode material prepared in Example 1.

[0053] Figure 2 SEM image of the cathode material prepared in Example 1;

[0054] Figure 3 The graph shows the cycle performance of the coin cell assembled with the cathode material in Example 1. Detailed Implementation

[0055] A modified zinc-iron-manganese base layered oxide includes a layered oxide matrix and a coating layer covering the surface of the layered oxide.

[0056] The chemical formula of the layered oxide matrix is ​​Na. a Zn x Fe y Mn z M 1-x-y-z O2;

[0057] Among them, 0.8 <a<1.02,0.05<x<0.4,0.34<y<0.8,0.1<z<0.5;

[0058] Preferably, a is 0.85–0.93, x is 0.15–0.25, y is 0.5–0.55, and z is 0.25–0.3.

[0059] The M includes, but is not limited to, one or more of Ni, Co, Ca, Mg, Al, Sc, Ti, V, Cr, Cu, Zr, Nb, Mo, Ta, W, and Re;

[0060] Preferably, M is a combination of Mg and Al, a combination of Ni and Mg, or a combination of Cu, Ni, and Mg;

[0061] The combination of Mg and Al, Ni and Mg, and Cu and Ni and Mg have a synergistic effect on structural stability. This may be because the introduction of different ions has a reconfiguration effect on the local electronic structure, which enhances the bond energy of Mn-O and Fe-O bonds.

[0062] The chemical formula of the coating layer is Mn3O4 and Na. b A is a composite coating layer, and b is the number of charges carried by A;

[0063] Where A is F - Cl - B4O7 2- BO3 3- P2O7 4- PO4 3- At least one of nonmetallic anions or anionic groups;

[0064] Preferably, A contains at least PO4. 3- More preferably, it is PO4. 3- and B4O7 2- The combination of .

[0065] The thickness of the Mn3O4 coating layer is approximately 1–5 nm, and Na… b The thickness of the A-coating layer is approximately 2-15 nm;

[0066] Preferably, the thickness of the Mn3O4 coating layer is 2–4 nm, and the Na… b The thickness of the A coating layer is 4-10 nm.

[0067] The molar ratio of Mn3O4 to the matrix material is 0.5%–5%, and Na… b The molar ratio of A to the matrix material is 0.2% to 3%;

[0068] Preferably, the molar ratio of Mn3O4 to the matrix material is 2%–4%, and Na… b The molar ratio of A to the matrix material is 1% to 2%;

[0069] The material described in this invention, through the combination of the bulk phase and the two coating materials, can stabilize the structure, suppress the decay of the matrix layered structure and the dissolution of iron; it can also suppress structural deterioration, irreversible phase transitions and Fe ion migration during cycling, thereby improving cycling stability. Furthermore, it helps improve the material's air stability, regulates the formation reaction, thickness and composition of CEI, and reduces gas generation and electrolyte side reactions.

[0070] The method for preparing the above-mentioned positive electrode material of the present invention includes the following steps:

[0071] (S1) Add sodium source, zinc source, iron source, manganese source and M source according to stoichiometric ratio, mix evenly to obtain mixture I;

[0072] (S2) Mixture I is subjected to two-stage sintering and one or more of air, oxygen or nitrogen is introduced. The first stage is calcined at 300-700℃ and held for 3-8 hours, and the second stage is calcined at 800-1200℃ and held for 7-20 hours. After cooling, the matrix material is obtained.

[0073] (S3) Add Mn3O4 to the matrix material and mix evenly to obtain mixture II; sinter mixture II and introduce one or more of air, oxygen or nitrogen, calcining at 300-700℃ for 3-8 hours; after cooling, obtain the first coating material;

[0074] (S4) Add non-metallic element anions or anionic group N source to the first coating material, mix evenly to obtain mixture III; sinter mixture III and introduce one or more of air, oxygen or nitrogen, calcining temperature 300-700℃, holding time 3-8h; quench treatment to obtain modified zinc-iron-manganese base layer oxide sodium-ion battery cathode material product.

[0075] The sodium source is selected from at least one of sodium carbonate, sodium nitrate, sodium bicarbonate, sodium hydroxide, sodium oxalate, sodium acetate, sodium peroxide, and sodium nitrite.

[0076] Preferably, it is at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium oxalate, and sodium acetate;

[0077] More preferably, it is a combination of sodium carbonate, sodium bicarbonate, and sodium hydroxide;

[0078] More preferably, the molar ratio of sodium content in sodium carbonate, sodium bicarbonate, and sodium hydroxide is 1:1:1.

[0079] The zinc source, iron source, manganese source, and M source are selected from at least one of the oxides, hydroxides, nitrates, carbonates, acetates, oxalates, sulfates, and hydrated compounds of zinc, iron, manganese, and M.

[0080] Preferably, it is an oxide, hydroxide, carbonate, acetate, or oxalate of zinc, iron, manganese, and M.

[0081] More preferably, it is an oxide, hydroxide, or carbonate of zinc, iron, manganese, and M.

[0082] In step (S1), except for the sodium source, all materials are fed according to the stoichiometric ratio of the chemical formula of the layered oxide sodium-ion battery cathode material. The sodium source is fed in excess of 3%-7% of the amount of Na in the stoichiometric ratio of the chemical formula of the layered oxide sodium-ion battery cathode material to compensate for the loss caused by sodium volatilization during calcination.

[0083] In steps (S1), (S2) and (S3), the method for achieving uniform mixing is mechanical mixing, co-precipitation, sand milling, or a combination of sand milling and spraying.

[0084] In step (S2), the atmosphere introduced is preferably oxygen or air;

[0085] More preferably, it is a mixture of oxygen and air;

[0086] A further preferred ratio is 20% oxygen and 80% air.

[0087] Step (S3), the atmosphere introduced is preferably nitrogen or air;

[0088] Step (S4), the atmosphere introduced is preferably oxygen;

[0089] The cooling method for steps (S2) and (S3) is furnace cooling, and the quenching method for step (S4) is liquid nitrogen cooling or dry ice cooling.

[0090] Furthermore, in step (S3), the source of non-metallic element anion or anionic group A includes, but is not limited to, solid acid and ammonium salt of non-metallic element anion or anionic group A.

[0091] Furthermore, this invention provides the application of the above-mentioned cathode material in the preparation of sodium-ion batteries.

[0092] The embodiments and examples of the present invention will be described in detail below. However, those skilled in the art will understand that the following embodiments and examples are for illustrative purposes only and should not be considered as limiting the scope of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention. Unless otherwise specified, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0093] Example 1

[0094] A method for preparing a layered oxide sodium-ion battery cathode material includes the following steps:

[0095] (S1) According to Na 0.9 Zn 0.16 Fe 0.5 Mn 0.27 Mg 0.05 Al 0.02 The chemical formula for O2 is as follows: Sodium source, zinc oxide, manganese tetroxide, iron oxide, magnesium oxide, and aluminum oxide are weighed out. The sodium source is a combination of sodium carbonate, sodium bicarbonate, and sodium hydroxide in a molar ratio of 1:1:1. The sodium source is in excess (compared to the stoichiometric excess) by 3.5%. After being sand-milled evenly, the mixture is spray-dried to obtain mixture I.

[0096] (S2) Mixture I is subjected to two-stage sintering and a mixture of 20% oxygen and 80% air is introduced. The first stage is calcined at 500°C and held for 5 hours, and the second stage is calcined at 1050°C and held for 15 hours. After cooling in the furnace, the matrix material is obtained.

[0097] (S3) Add spinel phase Mn3O4 (first coating material) at a molar ratio of 3.5% to the matrix material, and mechanically mix it evenly using a high-efficiency mixer to obtain mixture II; sinter mixture II and introduce air, calcining at 650℃ for 7.5h; after cooling in the furnace, the first coating material is obtained.

[0098] (S4) Add the second coating material (including ammonium borate and ammonium dihydrogen phosphate with a molar ratio of 0.5% to the matrix material) and mix them evenly by mechanical mixing with a high-efficiency mixer to obtain mixture III; sinter mixture III and introduce oxygen, calcining at 400℃ for 5h; after cooling with liquid nitrogen, the modified zinc-iron-manganese base layer oxide sodium-ion battery cathode material product is obtained.

[0099] Example 2

[0100] Compared to Example 1, the only difference is that the chemical formula of the matrix material is changed. The experimental groups are as follows:

[0101] Group A: M is Mg alone; the matrix chemical formula is Na. 0.9 Zn 0.18 Fe 0.5 Mn 0.27 Mg 0.05 O2;

[0102] Group B: M is Al alone; the matrix chemical formula is Na. 0.9 Zn 0.21 Fe 0.5 Mn 0.27 Al 0.02 O2;

[0103] Group C: M is a combination of Cu and Zr; the matrix chemical formula is Na. 0.9 Zn 0.16 Fe 0.5 Mn 0.27 Cu 0.05 Zr 0.02 O2;

[0104] Group D: M is a combination of Mg and Al; the matrix chemical formula is Na. 0.82 Zn 0.36 Fe 0.35 Mn 0.22 Mg 0.05 Al 0.02 O2; and the atmosphere during the sintering process is a mixture of 25% oxygen and 75% air. The first stage of calcination is carried out at 450°C and held for 6 hours, and the second stage of calcination is carried out at 1000°C and held for 18 hours. After cooling in the furnace, the matrix material is obtained.

[0105] All other operations and parameters are the same as in Example 1.

[0106] Example 3

[0107] Compared with Example 1, the only difference is that the conditions of step S3 are changed. Specifically, the amount of Mn3O4 is replaced with 2%; the sintering temperature is replaced with 500°C; and the sintering time is replaced with 6 hours.

[0108] All other operations and parameters are the same as in Example 1.

[0109] Example 4

[0110] Compared with Example 1, the only difference is that the conditions of step S4 are changed, and the experimental groups are as follows:

[0111] Group A: The second coating material is ammonium borate, and the amount of the second coating material used is the same as in Example 1;

[0112] Group B: The second coating material is ammonium dihydrogen phosphate, and the amount of the second coating material is the same as in Example 1;

[0113] Group C: The second coating material is ammonium chloride; and the amount of the second coating material is the same as in Example 1;

[0114] Group D: The amounts of ammonium borate and ammonium dihydrogen phosphate in the second coating material were both replaced to 1%, the sintering temperature was 500℃, and the time was 4 hours. After sintering, the material was placed in dry ice for rapid cooling.

[0115] All other operations and parameters are the same as in Example 1.

[0116] Comparative Example 1

[0117] Compared with Example 1, the only difference is that the coating in steps S3 and S4 was not performed, and the matrix in step S2 was directly used as the active material.

[0118] Comparative Example 2

[0119] Compared with Example 1, the only difference is that the coating in step S4 was not performed, and the first coating product in step S3 was directly used as the active material.

[0120] Comparative Example 3

[0121] Compared with Example 1, the only difference is that the coating in step S3 was not performed. Instead, the first coating product in step S2 was directly subjected to step S4, and the resulting product was used as the active material.

[0122] Comparative Example 4

[0123] Compared with Example 1, the only difference is that the product of S2 is pre-treated by step S4, and then treated by step S3, and the resulting product is used as the active material.

[0124] Comparative Example 5

[0125] Compared with Example 1, the only difference is that the chemical formula in step S1 is replaced with Na. 0.90 Zn 0.27 Mn 0.75 O2, and other preparation conditions are the same as in Example 1.

[0126] Comparative Example 6

[0127] Compared with Example 1, the only difference is that the chemical formula in step S1 is replaced with Na. 0.9 Mg 0.2 Fe 0.6 Mn 0.2 O2, and other preparation conditions are the same as in Example 1.

[0128] Comparative Example 7

[0129] Compared with Example 1, the only difference is that Mn3O4 in step S3 is replaced with MnO with the same molar amount of Mn, while the other preparation conditions are the same as in Example 1.

[0130] Comparative Example 8

[0131] Compared with Example 1, the only difference is that in step S4, ammonium borate and ammonium dihydrogen phosphate are replaced with magnesium oxide in the same molar amount as the second protective layer material, while the other preparation conditions are the same as in Example 1.

[0132] Comparative Example 9

[0133] Compared with Example 1, the only difference is that the cooling method in step S4 is replaced by furnace cooling, while the other preparation conditions are the same as in Example 1.

[0134] Comparative Example 10

[0135] Compared with Example 1, the only difference is that step S3 involves rapid cooling, while step S4 does not involve rapid cooling.

[0136] Sodium secondary battery performance test:

[0137] The active materials obtained from the above cases (freshly prepared, or freshly prepared materials stored in an Ar atmosphere), acetylene black (AB), and polyvinylidene fluoride (PVDF) were added to an N-methyl-2-pyrrolidone (NMP) solution in a molar ratio of 8:1:1. After grinding and dispersing, the slurry was uniformly coated onto aluminum foil and dried in a vacuum oven at 80°C for at least 10 hours to form the positive electrode sheet. Acetylene black was used as a conductive additive, polyvinylidene fluoride as a binder, and aluminum foil as a current collector. The positive electrode surface loading was approximately 2.5 mg / cm³. 2 .

[0138] In an argon-filled glove box with H2O and O2 concentrations below 0.1 ppm, 2032 coin cells were assembled. The electrolyte was a solution of 1 M NaPF6 dissolved in propylene carbonate (PC) and 5% fluoroethylene carbonate (PEC). Sodium foil was used as the negative electrode, and a glass fiber membrane was used as the separator for the half-cell, assembling a CR2032 coin cell. Testing was conducted using a constant current charge-discharge mode at a test chamber temperature of 25°C (cycle test temperature), a charging cutoff voltage of 4.0 V, a discharging cutoff voltage of 2.0 V, and activation at 0.1 C for 3 cycles, followed by 100 cycles at 1 C. The results are shown in Table 1.

[0139] Table 1. Comparison of electrochemical performance between examples and comparative examples.

[0140]

[0141]

[0142] Analysis: The data in the table show that the sodium-ion battery low-nickel oxide cathode materials prepared in Examples 1-4 exhibit high capacity and stability, fully activate and stabilize the Fe redox reaction, and suppress Fe dissolution and migration, demonstrating excellent electrochemical performance. Comparative Examples 1-4 lack the necessary processes, failing to fully activate the electrochemical activity of Fe and struggling to stabilize the structure and ensure reaction reversibility. Compared to Example 1, Comparative Examples 5 and 6 had an unreasonable element design, failing to achieve a stable Fe redox reaction, resulting in extremely poor cycle performance and rapid structural decay. Therefore, the selection of doping elements and the rational design of elemental composition can be considered key factors. Comparative Examples 7 and 8 did not use the coating material of this method, leading to deteriorated cycle performance. Therefore, the type of outermost coating layer can be considered a key factor. Compared to Example 1, Comparative Example 9 changed the cooling method in step S4, resulting in significantly reduced structural stability. Therefore, the cooling method can be considered a key factor. Comparative Example 10 did not use rapid cooling in step S4 but instead used rapid cooling in step S3, which failed to form a suitable structure in the final product, significantly affecting the activity and stability of Fe. Therefore, the rapid cooling stage can be considered one of the key factors.

Claims

1. A modified zinc-iron-manganese base oxide, characterized in that, It includes a matrix and a coating layer, wherein the chemical formula of the matrix is ​​Na. a Zn x Fe y Mn z M 1-x-y-z O2; where M is a transition metal element, 0.8 <a<1.02,0.05<x<0.4,0.34<y<0.8,0.1<z<0.5; The coating layer includes a first coating layer coated on the surface of the substrate and a second coating layer coating the first coating layer, wherein the material of the first coating layer is Mn3O4; and the material of the second coating layer is Na. b A is a nonmetallic anion or anionic group; b is the absolute value of the valence of A; In the modified zinc-iron-manganese matrix oxide, Mn3O4 accounts for 0.5-5% of the matrix molar amount; Na b A represents 0.2% to 3% of the matrix molar amount.

2. The modified zinc-iron-manganese base oxide as described in claim 1, characterized in that, In the matrix, M includes, but is not limited to, one or more of Ni, Co, Ca, Mg, Al, Sc, Ti, V, Cr, Cu, Zr, Nb, Mo, Ta, W, and Re; Preferably, M is a combination of Mg and Al, or a combination of Ni and Mg, or a combination of Cu, Ni, and Mg; Preferably, a is 0.85–0.93, x is 0.15–0.25, y is 0.5–0.55, and z is 0.25–0.

3.

3. The modified zinc-iron-manganese base oxide as described in claim 1, characterized in that, In the material of the second coating layer, A is F. - Cl - B4O7 2- BO3 3- P2O7 4- PO4 3- At least one of them; Preferably, A contains at least PO4. 3- Further preferred formulations include PO4. 3- and B4O7 2- .

4. A method for preparing the modified zinc-iron-manganese base oxide according to any one of claims 1-3, characterized in that, The matrix and Mn3O4 were mixed and calcined to coat the matrix with a Mn3O4 layer. Then, the matrix was mixed with an A precursor and calcined again, followed by rapid cooling to coat the Mn3O4 layer with Na in situ. b Layer A is used to prepare the modified zinc-iron-manganese base oxide; The precursor of A is the acid and / or ammonium salt of A.

5. The method for preparing the modified zinc-iron-manganese base oxide as described in claim 4, characterized in that, The matrix is ​​obtained by two-stage heat treatment of a mixed raw material containing sodium source, zinc source, iron source, manganese source and M source; wherein the two-stage heat treatment includes a first stage heat treatment holding process at a temperature of 300-700℃ and a second stage heat treatment holding process at a temperature of 800-1200℃. Preferably, the sodium source, zinc source, iron source, manganese source and M source are each at least one of the oxides, carbonates, nitrates and organic acid salts of their respective metal elements; Preferably, in the sodium source, zinc source, iron source, manganese source and M source, Zn, Fe, Mn and M in the zinc source, iron source, manganese source and M source are mixed in stoichiometric ratios according to chemical formulas, and the Na in the Na source is 1 to 1.1 times the stoichiometric molar amount; Preferably, the heat treatment holding time for the first stage is 3 to 8 hours, and the heat treatment holding time for the second stage is 7 to 20 hours.

6. The method for preparing the modified zinc-iron-manganese base oxide as described in claim 4 or 5, characterized in that, The calcination temperature is 300–700℃; Preferably, the holding time at the calcination temperature is 3 to 8 hours.

7. The method for preparing the modified zinc-iron-manganese base oxide according to any one of claims 4 to 6, characterized in that, The roasting temperature is 300–700℃; Preferably, the holding time at the calcination temperature is 3–8 hours; Preferably, rapid cooling is performed after roasting while the food is still in contact with a cooling medium; Preferably, the cooling medium is at least one of liquid nitrogen and dry ice; Preferably, the initial temperature difference for rapid cooling is above 200°C.

8. A positive electrode material for a sodium-ion battery, comprising a positive electrode active material, characterized in that, The positive electrode active material includes the modified zinc-iron-manganese base oxide as described in any one of claims 1 to 3 or the modified zinc-iron-manganese base oxide prepared by the preparation method described in any one of claims 4 to 7; Preferably, in the positive electrode active material, the content of the modified zinc-iron-manganese base oxide is above 50 wt.%. Preferably, the positive electrode material further comprises a conductive agent and a binder; Preferably, in the positive electrode material, the content of the conductive agent is less than 15 wt.% and the content of the binder is less than 15 wt.%.

9. A positive electrode for a sodium-ion battery, comprising a current collector and a positive electrode material composited thereon, characterized in that, The cathode material is the cathode material as described in claim 8.

10. A sodium-ion battery, comprising a positive electrode and a negative electrode, and a barrier material disposed between the positive electrode and the negative electrode, characterized in that, The positive electrode described herein is the positive electrode as described in claim 9.

Citation Information

Patent Citations

  • Coherent dual-phase type layered oxide positive electrode material of sodium-ion battery and preparation method of coherent dual-phase type layered oxide positive electrode material

    CN119230774A

  • Preparation method of multi-cation co-doped O3-NaNi1 / 3Fe1 / 3Mn1 / 3O2 layered sodium ion battery positive electrode material

    CN119230816A